2015
DOI: 10.1088/0004-637x/801/2/95
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Atmospheric Circulation of Warm and Hot Jupiters: Effects of Orbital Distance, Rotation Period, and Nonsynchronous Rotation

Abstract: Efforts to characterize extrasolar giant planet (EGP) atmospheres have so far emphasized planets within 0.05 AU of their stars. Despite this focus, known EGPs populate a continuum of orbital separations from canonical hot Jupiter values (0.03-0.05 AU) out to 1 AU and beyond. Unlike typical hot Jupiters, these more distant EGPs will not generally be synchronously rotating. In anticipation of observations of this population, we here present threedimensional atmospheric circulation models exploring the dynamics t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
146
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(171 citation statements)
references
References 113 publications
(204 reference statements)
24
146
1
Order By: Relevance
“…Our results have shown that the super-rotating equatorial jet, found as a solution for hot Jupiter atmospheres from several models (see for example Cooper & Showman 2005;Menou & Rauscher 2009;Rauscher & Menou 2010;Heng et al 2011;Dobbs-Dixon & Agol 2013;Parmentier et al 2013;Showman et al 2015;Helling et al 2016;Kataria et al 2016;Lee et al 2016), is robust in our setup. Our model does not include a drag or friction at the bottom boundary potentially responsible for removing some of the dependence on initial conditions (see Liu & Showman 2013;Cho et al 2015).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our results have shown that the super-rotating equatorial jet, found as a solution for hot Jupiter atmospheres from several models (see for example Cooper & Showman 2005;Menou & Rauscher 2009;Rauscher & Menou 2010;Heng et al 2011;Dobbs-Dixon & Agol 2013;Parmentier et al 2013;Showman et al 2015;Helling et al 2016;Kataria et al 2016;Lee et al 2016), is robust in our setup. Our model does not include a drag or friction at the bottom boundary potentially responsible for removing some of the dependence on initial conditions (see Liu & Showman 2013;Cho et al 2015).…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, although much progress has been made (and much more can yet be made) using 1D models, 3D models are required to truly unpick the observations, and extract robust physical meaning. E-mail: nathan@astro.ex.ac.uk Several GCMs (or similar models) with varying levels of sophistication have been applied to hot Jupiters (see for example Cooper & Showman 2005;Cho et al 2008;Menou & Rauscher 2009;Rauscher & Menou 2010;Heng et al 2011;Dobbs-Dixon & Agol 2013;Parmentier et al 2013;Showman et al 2015;Helling et al 2016;Kataria et al 2016;Lee et al 2016), including our own adaptation of the Met Office GCM termed the Unified Model (UM) (Mayne et al 2014a,b;Amundsen et al 2014;Helling et al 2016;Amundsen et al 2016Amundsen et al , 2017Boutle et al 2017). However, much of the progress has been driven by application of a single GCM, the SPARC/MITgcm.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the change in angular momentum from numerics and Rayleigh drag relative to the change in angular momentum from the Coriolis force, as a function of pressure. We compare both terms against the Coriolis force because it is a small term in the zonal momentum budget of hot Jupiters due to their slow rotation and winds that peak at the equator (Showman & Polvani 2011;Showman et al 2015). In relative terms, we find that the numerical change in angular momentum becomes t > (blue curves).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…We discretize the equations on the cubed-sphere grid,as described in Adcroft et al (2004),and use a horizontal fourth-order Shapiro filter in order to smooth horizontal noise (Shapiro 1970). This model has been successfully used to model hot Jupiteratmospheres over the past decade(e.g., Showman et al 2009Showman et al , 2013Showman et al , 2015Lewis et al 2010Lewis et al , 2014Kataria et al 2013Kataria et al , 2015Parmentier et al 2013).…”
Section: Global Circulation Modelmentioning
confidence: 99%